Gambaran Angka Kematian Larva Nyamuk Aedes aegypti dengan Pemberian Kulit Jeruk Purut (Citrus hystrix) Sebagai Larvasida Alami - Tuty Yuniarty; Reni Yunus (POLTEKKES KEMENKES YOGYAKARTA, 2018)
Dengue Fever (DF) and Dengue Haemorrhagic Fever (DHF) are infectious diseases caused by Dengue Virus and transmitted by the bite of Aedes Aegypti. One way to prevent the spreading of the DHF is by controlling its vectors. The best and most effective way to control the vector is with the eradication of Aedes aegypti larvae, which is called larviciding using temephos (abate powder). However, the application of temephos continually will pollute the environment and increase the resistance of larvae to pesticide so that natural pesticides are needed. One of them is by using Kaffir lime peel (Cytrushystric) which contains limonoids. Limonoid is known as toxic to the larvae of Aedes aegypti. The objective of this research is to find out the mortality rate of larvae with the concentrations of Kaffir lime peel as a natural pesticide. The method of this research is descriptive research, by using 200 Aedes aegypti larvae. Those larvae were divided into 3 concentrations of 3%, 5% and 7% of Kaffir lime peel with twice repetition and 1 % of temephos as a control. Each concentration contained 25 larvae in 100 ml of water. The observations were conducted by counting the dead larvae. The results showed that the average of the mortality rate of larvae at a concentration of 3% was 9 larvae (36%), a concentration of 5% were 21 of larvae (84%) and 7% were 24 of larvae (96%). It can be concluded that the mortality rate of Aedes Aegypti larvae by using Kaffir lime as natural larvacide at the concentration of 7% was the highest out of 3 concentrations with mortality of larvaewere 24 of 25 larvae (96%).